Glycated Albumin as Marker for Early Hyperglycemia Detection in Adolescent with β Thalassemia Major - Dewinda Candrarukmi; Annang Giri Moelyo; Muhammad Riza (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Hyperglycemia is one of the most common endocrine complications in children with β thalassemia major. Though the current diagnostic marker either requires fasting, has low reproducibility, or it is not an accurate for thalassemia patients. Glycated albumin (GA) is a quick and easy alternative marker for hyperglycemia detection and monitoring of glycemic control. However to date, no studies have analyzed the role of GA value in detection of hyperglycemia in children with thalassemia major. This study analyzed the value of GA as an alternative screening marker for hyperglycemia detection in children with β thalassemia major.METHODS: A single-blind prospective diagnostic test was conducted in 9 to 18 years old children with β thalassemia major and who were treated at the Dr. Moewardi Regional General Hospital between October 1, 2018 and December 31, 2019. In a single, fasted study visit, height, weight, fasting blood glucose (FPG), GA, oral glucose tolerance test (OGTT) were measured. The area under a receiver operating characteristic curve (AUC) was used to determine the cut-off value at which hyperglycemia prediction (OGTT ≥140 mg/dL) display optimal sensitivity and specificity. RESULTS: Among the 53 children with β thalassemia major, 1 (1.9%) had diabetes mellitus and 4 (7.5%) had prediabetes based on their OGTT values. The median GA value in this study was 10.9% (range: 7.6–12.4%). GA had a low AUC (0.646, p=0.287) for hyperglycemia detection in pediatric patients with β thalassemia major. At a cut-off of 11.45%, GA demonstrated 60% sensitivity and 60.4% specificity.CONCLUSION: GA cannot be used as an alternative marker for hyperglycemia detection in children with β thalassemia major.KEYWORDS: hyperglycemia, diabetes mellitus, prediabetes, β thalassemia major, glycated albumin